Mons. Enrique Angelelli, Witness Of Faith (Teología, 2015)
This reflection on the third bishop of La Rioja is located in the context of the nihil obstat of the Congregation for the Causes of Saints in order to begin the process of beatification. This leads to look some steps describing his pastoral work in the diocese, with the aim of knowing the Testimony he gave on the way to death. Given that the apostolate of Mons. Angelelli took place in a controversial political scene, this article studies some responses with which he illuminated this historical juncture.
Keywords: Enrique Angelelli; Beatification; Testimony; Political Scene; Responses